Kebahagiaan Menurut Para Filsuf - Munawir Haris (LPPM IAIN Sorong, 2016)
Happiness is not the same as joy or pleasure. The happiness is a condition that lasts (a lasting condition) and not a feeling or emotion that passed. In general, a person may feel happy even though he was suffering from grief, as well as someone who is experiencing chronic unhappiness can also know the moments of joy. Also happiness is not a disposition or attitude merry soul although not denying that these things can help towards happiness. Some people can have such behavior even in the face of disappointment. Someone is perfectly happy because he has a good full and perfect. Perfect happiness that comes and fully satisfy all our desires, while happiness is called incomplete if it does not satisfy all our desires or, suppose can satisfy all the desires, but are not satisfy with fully. To avoid confusion, it should be noted in earnest here that the moral philosophy of happiness natural look only (natural happiness). Natural happiness is satisfying all desires are included and appears on the naked human nature (man’s bare nature). This article talks about the concept of happiness according to the philosophers.